ANALISIS PROSEDUR PENAGIHAN BIAYA OPERASIONAL DI PT PLN (PERSERO) UPT PURWOKERTO - Alisia Mandasari; S.S Atmadja (PUTRA JAWA PUBLISHER, 2023)
Direct procurement is the implementation of the procurement of goods or services carried out by purchasing or paying directly to the provider of goods or services by procurement officials without an auction process. CV Cortheo is one of the direct procurement vendors at PT PLN (Persero) UPT Purwokerto. After the work is completed, the vendor bills for operational costs after the work period ends. When billing the documents prepared take a relatively long time with relatively many documents, this is due to the large number of parties involved in the billing administration process, therefore it is necessary to centralize payments called the Vendor Invoicing Portal (VIP) to simplify the billing process in one door. This research method uses a qualitative descriptive method with a case study approach that occurs within the company, which is carried out systematically to collect, process and conclude existing data. The purpose of this study was to determine the operational cost billing procedure at PT PLN (Persero) UPT Purwokerto. The results of this study indicate that the old system billing process takes a long time, while the centralization of payments called the Vendor Invoicing Portal (VIP) makes the billing process more transparent, structured effective and efficient for vendors.